Bayesian estimation of the beta distribution parameter (α) when the parameter (β) is known (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, the Bayesian estimation was used to estimate the parameter of the beta distribution (α) when (β = 1), (2 = β) and (3 = β). By employing the Monte Carlo simulation method, the simulation was tested with different sample sizes (10, 20, 25, 40, 75, 100) and based on the MSE statistical standard), where the best estimator for parameter (α) was found when (β = 1 )